6′-O-Galloylpaeoniflorin Attenuates Osteoclasto-genesis and Relieves Ovariectomy-Induced Osteoporosis by Inhibiting Reactive Oxygen Species and MAPKs/c-Fos/NFATc1 Signaling Pathway - Liu, Wenjie; Xie, Gang; Yuan, Guixin; Xie, Dantao; Lian, Zhen; Lin, Zihong; Ye, Jiajie; Zhou, Wenyun; Zhou, Weijun; Li, Henghui; Wang, Xinjia; Feng, Haotian; et al. (Frontiers in Pharmacology, 2021)
Emerging evidence suggests bright prospects of some natural antioxidants in the treatment of osteoporosis. 6′-O-Galloylpaeoniflorin (GPF), an antioxidant isolated from peony roots (one of very widely used Oriental medicines, with various anti-inflammatory, antitumor, and antioxidant activities), shows a series of potential clinical applications. However, its effects on osteoporosis remain poorly investigated. The current study aimed to explore whether GPF can attenuate osteoclastogenesis and relieve ovariectomy-induced osteoporosis via attenuating reactive oxygen species (ROS), and investigate the possible mechanism. After the culture of primary murine bone marrow-derived macrophages/monocytes were induced by the use of macrophage colony-stimulating factor (M-CSF) and the receptor activator of NF-κB ligand (RANKL) and then treated with GPF. Cell proliferation and viability were assessed by Cell Counting Kit-8 (CCK-8) assay. Thereafter, the role of GPF in the production of osteoclasts and the osteogenic resorption of mature osteoclasts were evaluated by tartrate-resistant acid phosphatase (TRAP) staining, podosome belt formation, and resorption pit assay. Western blotting and qRT-PCR examination were performed to evaluate proteins’ generation and osteoclast-specific gene levels, respectively. The ROS generation in cells was measured in vitro by 2',7'-Dichlorodi-hydrofluorescein diacetate (DCFH-DA). Ovariectomy-induced osteoporosis mouse administered with GPF or vehicle was performed to explore the in vivo potential of GPF, then a micro-CT scan was performed in combination with histological examination for further analysis. GPF suppressed the formation of osteoclasts and podosome belts, as well as bone resorption when induced by RANKL through affecting intracellular ROS activity, MAPKs signaling pathway, and subsequent NFATc1 translocation and expression, as well as osteoclast-specific gene expression in vitro. In vivo study suggested that exposure to GPF prevented osteoporosis-related bone loss in the ovariectomized mice. These findings indicate that GPF attenuates osteoclastogenesis and relieves ovariectomy-induced osteoporosis by inhibiting ROS and MAPKs/c-Fos/NFATc1 signaling pathway. This suggested that GPF may be potentially used to treat bone diseases like periodontitis, rheumatoid arthritis, and osteoporosis associated with osteoclasts.